Compatibility of ten isolates of Beauveria bassiana (Balsamo) Vuillemin with four commonly used fungicides in Thailand - Krutmuang, Patcharin; Pittarate, Sarayute; Rahman, Aroja; Rajula, Julius; Thungrabeab, Malee (Fundamental and Applied Agriculture, 2019)
The use of Beauveria bassiana (Balsamo) Vuillemin (Phylum: Ascomycota: and Order: Hypocreales) has greatly increased due to its broad spectrum of pathogenic activity. This fungi has been studied intensively for the purpose of developing mycoinsecticides that can be integrated with other agrochemicals in the management of insect pests in rice fields. Additionally, its use in crops other than rice is being studied. This study investigated the effect of four fungicides viz. mancozeb, propineb, propiconazole, and pifenoconazole, on the growth of 10 isolates of B. bassiana under laboratory conditions. Malt extract agar (MEA) amended with the fungicides at two rates (recommended and half-rate) where recommended rates were as follows: mancozeb (15 g 20 L−1 of water), propineb (55 g 20 L−1 of water), propiconazole (25 mL 20 L−1 of water) and difenoconazole (40 m 20 L−1 of water) were used to culture the isolates of the fungus. It was observed that propiconazole and difenoconazole consistently exerted a strong inhibitory effect on the mycelial growth of the B. bassiana isolates. On the other hand, the isolates of B. bassiana tested exhibited low to moderate sensitivity to mancozeb and propineb. B. bassiana isolate BCMU 2 displayed low to moderate sensitivity to mancozeb, propineb, and difenoconazole. This study suggests that mancozeb and propineb may have the potential for use in combination with B. bassiana in integrated pest management programs for simultaneous control of insect pests and plant diseases.